Sekolah Dan Arena Konflik: Kritik Sosial Film Pengepungan Di Bukit Duri - Oska Miranda; Aliasa Aliasan; Lilis Sukmawati (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study is entitled School as an Arena of Conflict: Social Criticism in the Film Pengepungan di Bukit Duri.” This research employs a descriptive qualitative research method. Pengepungan di Bukit Duri is a film that represents the reality of social conflicts occurring within the school environment. The purpose of this study is to identify the forms of social criticism and to analyze how schools are represented as arenas of conflict in the film. This study uses a qualitative approach with documentation techniques for data collection. The documentation technique involves collecting data in the form of scenes, dialogues, and plot elements in the film that relate to conflict and social criticism. The data analysis technique applied in this research is Roland Barthes semiotic analysis, which divides meaning into denotation, connotation, and myth. The results of this study indicate that there are several forms of social conflict depicted in the film, including interpersonal conflict, intergroup conflict, and structural conflict within the school environment. The film portrays the school as an arena of conflict characterized by power imbalances, violence, weak protection for teachers, and failures in the educational system. This shows that film functions not only as a medium of entertainment but also as a medium for conveying messages and social criticism of realities occurring in society.